Longitudinal dispersion of tracer particles in a channel bounded by Porous media using slip condition - Dulal Pal; R. Veerabhadraiah; P. N. Shivakumar; N. Rudraiah (International Journal of Mathematics and Mathematical Sciences)
Longitudinal dispersion of solute in a channel bounded by porous layers is studied using the analysis of Taylor [4] with BJ slip condition. The results of the present analysis are compared with those of Fung and Tang [2] obtained from using the no-slip condition. It is found that the effect of slip is significant only in the case when the membrane is permeable to solvent but not to the tracer. However, in the case when the membrane is permeable to both the tracer and the solvent, we find that our results coincide with those of Fung and Tang [2].